Jake just does scribbles but I do pictures : drawing self-efficacy and the messages four to nine-year-old children give and receive about their drawing : a thesis presented in partial fulfilment of the requirements for the degree of Masters in Education at Massey University - Richards, Rosemary D (Massey University, 2003)
This study investigates the drawing self-efficacy of 136 four to nine-year-olds and the messages they gave and received about their art. Participants responded to a 36-question questionnaire, informed by Bandura's self-efficacy theory (1986). Thirty-five children were interviewed, and 48 were observed. Analysis of the questionnaires revealed that drawing self-efficacy scores ranged from low to high. Over half of the sample had quite high to high drawing self-efficacy. Statistical analyses revealed no significant differences in terms of gender or year levels. However, the Gender by Year Level interaction effect for drawing self-efficacy was statistically significant. The greatest effect size occurred between boys and girls at year four level where boys scored over 1 standard deviation unit lower than the mean, and at new entrant level where boys scored almost 1 standard deviation unit lower than the mean. At the year two level the boys were almost three-quarters of a standard deviation unit above the mean. Analyses revealed significant differences for subscales on preferences, levels of difficulty, emotional responses, vicarious experiences, and effort and persistence. Data for preferences showed that girls were more likely to choose art activities than boys, and year two children showed the highest preference for art activities while kindergarten children showed the lowest. At the same time there was a general trend towards a decline in drawing confidence as the year levels increased, as shown by responses to items on levels of difficulty. Overall, drawing was an emotionally positive experience except at year four level, where the boys where over one standard deviation unit lower than the mean. Year two children had the highest emotional responses to drawing and year four children had the lowest. Findings suggested that younger children responded more positively to vicarious experiences than older children, believing themselves capable of drawing competently if others could. New entrant girls showed the highest level of effort and persistence, and year four boys the lowest. In general, friends, family and teachers gave positive messages to children about their drawings. Some children linked drawing competency with reading ability and data revealed a statistically significant Reading Age by Year Level interaction effect for drawing self-efficacy. Data suggests that at years two and three there was a positive relationship between high reading age and drawing self-efficacy scores. In year four the inverse was observed. However, statistically significant contrasts were not identified. Several themes and messages emerged from observations and interviews. In the kindergarten proportionally more girls than boys engaged in art activities. Self-selected interactions in both sites favoured same-sex groupings, and in general girls commented more positively about each other's drawings than boys did. Regardless of gender, children with high drawing self-efficacy appeared more confident and gave and received more positive messages than children with lower drawing self-efficacy. Children commented on scribbling and linked drawing to reading and writing abilities. Teachers did not comment about the right and wrong ways to draw, but children measured success by external rewards and by criteria applied to other curriculum areas. Children were critical of each other's drawings and at times the teacher's neutral comments were re-interpreted as negative comments. Emotional responses to art were also linked to patterns of friendship. Children, at all levels, emphasised effort over ability as a reason for success with drawing. Children who had a reputation for drawing specific topics often displayed higher drawing self-efficacy than age peers, and by year three the issues of ownership of ideas and copying were apparent. At both sites children provided a greater source of verbal persuasion than teachers. The teachers were positive at all times, although they tended to praise appropriate behaviour rather than comment on elements of the drawings. In general children with the highest drawing self-efficacy were the most resilient to negative messages and experiences. Findings did not support a strong relationship between teachers' comments and levels of drawing self-efficacy. However there was some support for the view that children's drawing self-efficacy declines once a child attends school, when gender and year level are both considered. In this sample the girls had an increase in drawing self-efficacy when they started school that dropped marginally in year one, but then continued to increase with age. On the other hand the boys had a drop in drawing self-efficacy on starting school, that then increased until year two, and then took a sharp decline. Qualitative data tended to support these findings. Recommendations for instructional practices in schools and kindergartens include a focus on participation, theme and inquiry-based programmes, critiquing of artworks, children teaching children, teacher professional development, and understanding drawing self-efficacy levels of children.
Keywords: Self-efficacy; Drawing ability in children